Studi Pemikiran Pendidikan Islam Perspektif Naquib al-Attas - Savira Rahmania; M. Yunus Abu Bakar (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Education is an important part of human life. In particular, Islamic Education with its various patterns that are oriented towards providing supplies to humans to achieve happiness in the world and the hereafter. Islamic education is an education system that strives to produce knowledgeable people in accordance with Islamic ideals that can change the way of looking at individuals to be better from all sides, both from the way of thinking, speaking and character. This research analyzes the thoughts of Syed Muhammad Naquib Al-Attas about the study of Islamic education thought from the perspective of Naquib a-attas. This research is qualitative descriptive with a library research approach that focuses more on collecting data from various relevant data sources. In this case, it includes books, articles, journals and the internet, and research results that are relevant to the title of this scientific work. Syed Muhammad Naquib Al-Attas defines education as a key concept that is the core of education and the educational process. The curriculum of Syed Muhammad Naquib Al-Attas is: fardu ain and fardu kifayah, namely Islamic education and science education. This is also similar to the division of knowledge in education in Indonesia, namely religious science, social science and science. Keywords: educational thought, Islamic education, naquib al-attas.